Impact Analysis of Rubber Factory PT. Bangkinang Village Community in Metro Central Tangkerang Pekanbaru - Rissa Amanila; Sofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study was conducted in March 2013 in the Rubber Factory PT. Bangkinang Village Middle Tangkerang Pekanbaru. This study berujuan to know or meminimalisirkan negative impacts such as odors from waste rubber factory itself and to determine the factors that influence it.While data collection techniques in research with direct observations in the field and called observation, collection of data obtained through interviews with the Director of the rubber factory of PT. Bangkinang, employees and the communities residing around the factory rubber and literature, with data analysis using qualitative descriptive analysis. It is also used SWOT analysis is used to see and study the factors that became strengths and weaknesses as well as the factors that are an opportunity and a threat to the rubber factory of PT. Bangkinang along with the surrounding community.From these results it can be concluded that the rubber factory of PT. Bangkinang Village Middle Tangkerang Pekanbaru based on the SWOT analysis, the position or location of the rubber factory of PT. Bangkinang now in the wrong place due to the dense population. Keywords: Policy, Analysis and Impact